2019
DOI: 10.1002/mame.201800776
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Single‐Cell Encapsulation Using E‐Jet 3D Printing with AC‐Pulsed Modulation

Abstract: With the growing therapeutic importance of cell microcarriers, there has been a rise in the need to develop technologies that facilitate efficient microencapsulation of cells, currently limited by a lack of straightforward and low‐cost strategies for single‐cell isolation and printing. Thus, the aim of this study is to develop a gentle and cell‐compatible electro‐hydrodynamic jet 3D printing technique to facilitate the efficient microencapsulation of cells in hydrogel microspheres, and investigate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…The drug-loaded PLGA-DOX-5FU (PD5) scaffolds were fabricated using our electro-hydrodynamic jet (E-jet) 3D printing system 42 , 43 and characterized by micro-CT and scanning electron microscopy (SEM; Figure S1 , Figure S2 ). To ensure pH responsiveness, the PD5 scaffolds were sandwiched between a GC gel to fabricate the intelligent scaffold (IS) (Figure 1 ), which were shown to be completely wrapped by the gel (Figure 2 A, Figure S3 , and Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The drug-loaded PLGA-DOX-5FU (PD5) scaffolds were fabricated using our electro-hydrodynamic jet (E-jet) 3D printing system 42 , 43 and characterized by micro-CT and scanning electron microscopy (SEM; Figure S1 , Figure S2 ). To ensure pH responsiveness, the PD5 scaffolds were sandwiched between a GC gel to fabricate the intelligent scaffold (IS) (Figure 1 ), which were shown to be completely wrapped by the gel (Figure 2 A, Figure S3 , and Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides droplets, microfluidics can also generate microgels by adding a hydrogel precursor to the cell suspension. Although the majority use microfluidics as the main technique to form microgels, there are other methodologies, such as manual drop-wise encapsulation, [74][75][76] acoustic systems, [77,78] jet printing, [79] hydroelectric atomization, [36] among others (Figure 3). This approach is usually preferred over the previous method, due to microgel robustness and durability, being more suitable for disease modeling or tissue engineering purposes.…”
Section: Hydrogel-based Encapsulationmentioning
confidence: 99%
“…However, the diameter of the droplets was more than 300 µm under different printing parameters. Wang et al utilized AC-pulse-modulated voltage to periodically eject hydrogel droplets which were deposited precisely in predesigned patterns on the substrate (figures 10(e) and (f)) [145]. They studied the effect of five different nozzle-to-collector distances (2, 3, 4, 5, and 6 mm) on EHD printing process and found that the diameter of droplets can be stably controlled ranging from 150 µm to 600 µm with high cell viabilities.…”
Section: Controlled Ehd Bioprinting Of Cell-laden Microgel Patternsmentioning
confidence: 99%